2014
DOI: 10.1016/j.cbpb.2013.12.006
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference mediated knockdown of the KDEL receptor and COPB2 inhibits digestion and reproduction in the parasitic copepod Lepeophtheirus salmonis

Abstract: Retrograde transport of proteins from the endoplasmic reticulum to the Golgi is an essential part of the secretory pathway that all newly synthesised secreted and membrane proteins in eukaryotic cells undergo. The aim of this study was to characterise two components of the retrograde transport pathway in the parasitic copepod Lepeophtheirus salmonis (salmon louse) on a molecular and functional level. LsKDELR and LsCOPB2 were confirmed to be the salmon louse homologues of the chosen target proteins by sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…This showed that the LsAst1 primers amplified a second gene, EMLSAG00000011131. The in situ hybridization was performed with sections from adult female lice according to Dalvin et al (), with some modifications as described in Tröße et al (). Additionally, the proteinase K treatment was prolonged to 18 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…This showed that the LsAst1 primers amplified a second gene, EMLSAG00000011131. The in situ hybridization was performed with sections from adult female lice according to Dalvin et al (), with some modifications as described in Tröße et al (). Additionally, the proteinase K treatment was prolonged to 18 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…In situ hybridization was performed according to Dalvin et al [36] , with some modifications as described in Tröße et al [37] . The digoxigenin labelled (DIG-labelled) sense and antisense RNA probes were made with primers listed in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In insects, knock down of chitinase has been shown to be essential for hatching, molting and adult eclosion (Zhang et al, 2012;Zhu et al, 2008). The use of RNAi in salmon louse has been reported several times (Campbell et al, 2009;Dalvin et al, 2009;Eichner et al, 2014;Trösse et al, 2014). RNAi of a chitinase in crustaceans has to our knowledge only been reported once in salmon louse (Eichner et al, 2014).…”
Section: Introductionmentioning
confidence: 94%